2022
DOI: 10.3389/fonc.2021.810387
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating Agent-Based Combination Therapies to Treat Post-Hematopoietic Stem Cell Transplant Relapse of Acute Myeloid Leukemia

Abstract: Allogeneic stem cell transplantation still represents the best curative option for most patients with acute myeloid leukemia, but relapse is still dramatically high. Due to their immunologic activity and safety profile, hypomethylating agents (HMAs) represent an interesting backbone for combination therapies. This review reports mechanism of action, safety, and efficacy data on combination strategies based on HMAs in the setting of post-allogeneic stem cell transplant relapse. Several studies highlighted how H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…However, relapse remains the primary cause of mortality in patients receiving allo-HSCT for MDS or AML ( 3 , 4 ). Epigenetic agents, mainly including hypomethylating agents (HMAs) and histone deacetylase inhibitors (HDACi), have become widely used in the pretransplant, transplant, and posttransplant stages for MDS or AML ( 5 9 ) and are regarded as candidates to reduce the tumor burden, as they have tolerable toxicity and mitigate graft-versus-host disease (GvHD) without influencing graft versus leukemia (GvL) ( 9 , 10 ). Furthermore, HMAs have been proven effective in exerting an antitumor effect by promoting cell differentiation and apoptosis in leukemia cells ( 11 , 12 ) and by reactivating silent tumor suppressor antigens like MAGE-1 and WT-1 to improve the response to other therapeutic hematologic malignancies ( 10 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, relapse remains the primary cause of mortality in patients receiving allo-HSCT for MDS or AML ( 3 , 4 ). Epigenetic agents, mainly including hypomethylating agents (HMAs) and histone deacetylase inhibitors (HDACi), have become widely used in the pretransplant, transplant, and posttransplant stages for MDS or AML ( 5 9 ) and are regarded as candidates to reduce the tumor burden, as they have tolerable toxicity and mitigate graft-versus-host disease (GvHD) without influencing graft versus leukemia (GvL) ( 9 , 10 ). Furthermore, HMAs have been proven effective in exerting an antitumor effect by promoting cell differentiation and apoptosis in leukemia cells ( 11 , 12 ) and by reactivating silent tumor suppressor antigens like MAGE-1 and WT-1 to improve the response to other therapeutic hematologic malignancies ( 10 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may crucially contribute to the development of drug resistance [ 94 ]. In summary, their immunomodulatory properties make them an interesting backbone for combination therapies [ 95 ]. Especially since combination therapies might comprise the possibility to bypass drug resistance mechanisms.…”
Section: Immunomodulation In Amlmentioning
confidence: 99%
“…Combination trials of ivosidenib or enasidenib with AZA in relapsed or refractory AML (NCT03683433) as well as in first-line therapy of IDH mut AML with enasidenib (AML005-trial) or ivosidenib (AGIL-trial) in combination with AZA (NCT02677922) are currently ongoing [ 97 , 98 ]. Even in the posttransplant setting several studies showed the benefit of the combination of DLIs and AZA, further randomized trials are, up to date, still lacking [ 95 ]. Additionally, the therapy with DLIs and AZA can be enhanced with venetoclax in the posttransplant setting [ 95 ].…”
Section: Immunomodulation In Amlmentioning
confidence: 99%
See 2 more Smart Citations